Teachers challenging experiences in executing new policy initiatives: Implications for refining policy implementation towards achieving world-class education - Abdul Razak, A.Z. (2011)
The aim of this study was to identify the challenges that teachers faced in implementing new educational policies. Data were Collected through interviews with selected teachers in two secondary Schools in Malaysia. In total 24 participants were involved in this study. Data analysis was carried out through analytic categories based on hermeneutics philosophy. The findings indicated that teachers face various challenges during the implementation of the national education Policy that derived from The attitudes and abilities of students, School work environment, Parents placing excessive demands on teachers, challenges arising from the Ministry of Education and The actions of the Senior Management Teams in imposing additional duties on teachers . The data from this study could assist policy makers inshaping the Implementation of a new policy in ways that put less pressure for teachersin order to enhance positive implications from the policy implementation that can lead to achievement of world-class education.